Just-in-Time Training for High-Risk Low-Volume Therapies: An Approach to Ensure Patient Safety. Issue 1 (January 2016) - Helman, Stephanie; Lisanti, Amy Jo; Adams, Ann; Field, Cynthia; Davis, Katherine Finn
Abstract : High-risk low-volume therapies are those therapies that are practiced infrequently and yet carry an increased risk to patients because of their complexity. Staff nurses are required to competently manage these therapies to treat patients' unique needs and optimize outcomes; however, maintaining competence is challenging. This article describes implementation of Just-in-Time Training, which requires validation of minimum competency of bedside nurses managing high-risk low-volume therapies through direct observation of a return-demonstration competency checklist. Abstract : Supplemental Digital Content is Available in the Text.